Makna Simbol Budaya Mandailing dalam Pembentukan Empati Anak pada Keluarga Islam di Desa Kayu Laut - Rambe, Khairul Mufti; Lubis, Amru Syahputra; Nasution, Khoiruddin; Ramadhona, Suci; Granady, Seflin; Rinjani, Quinta Abisekha Utari; Putri, Dhea Annisa (Sociology Department Of Syiah Kuala University, 2025)
This study aims to explore how Mandailing cultural symbols are interpreted and practiced within Islamic families, and how these symbols contribute to the development of childrens empathy amid social change. Symbols such as Dalihan Na Tolu, marbagas, and umpasa serve as vehicles for transmitting values of compassion, respect, and social responsibility. Within Mandailing society, where Islamic values such as rahmah and adab coexist with local traditions, families become dialectical spaces for culturally contextualized character education. The research was conducted in Kayu Laut Village, Mandailing Natal Regency, using a qualitative approach with Interpretative Phenomenological Analysis (IPA) to examine the symbolic meanings embedded in the lived experiences of seven Mandailing Muslim families. Data were collected through in-depth interviews, participant observation, and cultural documentation. The findings reveal that symbolic cultural practices function as effective pedagogical tools for internalizing empathy through emotionally and socially rich experiences. Despite the pressures of modernization, families demonstrate active resistance by reconstructing symbolic practices while preserving their core values. This study contributes to the fields of cultural sociology and Islamic character education, and emphasizes the importance of culturally rooted strategies in family-based education.AbstrakPenelitian ini bertujuan untuk memahami bagaimana simbol-simbol budaya Mandailing dimaknai dan dipraktikkan dalam keluarga Islam, serta bagaimana simbol tersebut berkontribusi terhadap pembentukan empati anak di tengah perubahan sosial. Simbol-simbol seperti Dalihan Na Tolu, marbagas, dan umpasa berperan sebagai medium internalisasi nilai kasih sayang, penghormatan, dan tanggung jawab sosial. Dalam konteks masyarakat Mandailing yang juga religius, nilai-nilai Islam seperti rahmah dan adab berjalan seiring dengan adat, menciptakan ruang pendidikan karakter yang bersifat dialektis dan kontekstual. Penelitian ini dilakukan di Desa Kayu Laut, Kabupaten Mandailing Natal, dengan pendekatan kualitatif dan metode Interpretative Phenomenological Analysis (IPA), untuk menggali makna simbolik dari pengalaman subjektif tujuh keluarga Mandailing Muslim. Data diperoleh melalui wawancara mendalam, observasi partisipatif, dan dokumentasi simbolik budaya. Hasil penelitian menunjukkan bahwa praktik simbol budaya menjadi wahana internalisasi empati melalui keterlibatan sosial anak yang emosional dan reflektif. Meskipun modernisasi menghadirkan tantangan, keluarga mampu melakukan resistensi aktif dengan merekonstruksi simbol budaya tanpa menghilangkan nilai intinya. Penelitian ini memberikan kontribusi pada kajian sosiologi dan pendidikan karakter Islam, serta mengusulkan perlunya penguatan pendekatan berbasis budaya dalam strategi pendidikan keluarga.